2022
DOI: 10.3390/pharmaceutics14050998
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Barriers and Their Influence on Gene Therapy Products Delivery

Abstract: The eye is formed by tissues and cavities that contain liquids whose compositions are highly regulated to ensure their optical properties and their immune and metabolic functions. The integrity of the ocular barriers, composed of different elements that work in a coordinated fashion, is essential to maintain the ocular homeostasis. Specialized junctions between the cells of different tissues have specific features which guarantee sealing properties and selectively control the passage of drugs from the circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Collagen fibers from the hydrophilic stroma also limit the penetration of therapeutic proteins, which usually takes place via pinocytosis or endocytosis (active transport mechanism) [ 55 , 56 ]. The tight junctions present in the cornea, sclera, and retina significantly prevent the diffusion of hydrophilic large macromolecules [ 56 , 57 ].…”
Section: Ocular Barriers and Approaches To Ocular Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen fibers from the hydrophilic stroma also limit the penetration of therapeutic proteins, which usually takes place via pinocytosis or endocytosis (active transport mechanism) [ 55 , 56 ]. The tight junctions present in the cornea, sclera, and retina significantly prevent the diffusion of hydrophilic large macromolecules [ 56 , 57 ].…”
Section: Ocular Barriers and Approaches To Ocular Administrationmentioning
confidence: 99%
“…Collagen fibers from the hydrophilic stroma also limit the penetration of therapeutic proteins, which usually takes place via pinocytosis or endocytosis (active transport mechanism) [ 55 , 56 ]. The tight junctions present in the cornea, sclera, and retina significantly prevent the diffusion of hydrophilic large macromolecules [ 56 , 57 ]. The tight junctions in the conjunctival epithelium are usually wider than those in the corneal epithelium but are still unable to provide penetration of large molecules [ 58 , 59 ].…”
Section: Ocular Barriers and Approaches To Ocular Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increasing number of studies have shown that the behavior of cells on two-dimensional (2D) substrates is distinctly different from that on three-dimensional (3D) ECMs in vivo. Moreover, type I collagen and fibronectin, two major classes of ECM proteins, are fibrous and form “mesh-like” 3D microenvironments [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method is less invasive and relatively safe while potentially providing widespread gene transfer throughout the entire retinal surface area (Duncan et al., 2018). One caveat is that a relatively high gene therapy dose would be needed due to the presence of a series of delivery barriers encountered in this administration route, such as the vitreous gel and inner limiting membrane (ILM) (Leclercq, Mejlachowicz, & Behar‐Cohen, 2022; Mains & Wilson, 2013; Zhang & Johnson, 2021a). This aspect is of particular concern for virus‐based gene‐delivery platforms (e.g., AAV) as the necessity of large viral doses creates significant issues of safety, immunogenicity, and economic burden (Timmers et al., 2020).…”
Section: Introductionmentioning
confidence: 99%